2018
DOI: 10.1111/odi.12804
|View full text |Cite
|
Sign up to set email alerts
|

A novel PITX2 mutation in non‐syndromic orodental anomalies

Abstract: This study for the first time demonstrates that the PITX2 mutation could lead to non-syndromic orodental anomalies in humans. We propose that the specific location in the C-terminal domain of PITX2 is exclusively necessary for tooth development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…In humans, PITX2 mutants are generally associated with ARS, which manly affects the development of the eyes, teeth and abdomen (Vieira et al, 2006). Notably, for the first time, a frameshift deletion, c.573_574delCA (p.L193QfsX5) in PITX2 was found to cause nonsyndromic dental anomalies in humans (Intarak et al, 2018). Interestingly, our study revealed a previously reported PITX2 nonsense mutation (Y121X), which was identified in patients with ARS (Vieira et al, 2006), that is NM_000325:c.522C > G (p.Y174*) in our study, was found to be related to nonsyndromic TA in family 8.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, PITX2 mutants are generally associated with ARS, which manly affects the development of the eyes, teeth and abdomen (Vieira et al, 2006). Notably, for the first time, a frameshift deletion, c.573_574delCA (p.L193QfsX5) in PITX2 was found to cause nonsyndromic dental anomalies in humans (Intarak et al, 2018). Interestingly, our study revealed a previously reported PITX2 nonsense mutation (Y121X), which was identified in patients with ARS (Vieira et al, 2006), that is NM_000325:c.522C > G (p.Y174*) in our study, was found to be related to nonsyndromic TA in family 8.…”
Section: Discussionmentioning
confidence: 99%
“…We detected the expression of KMT2D and KDM6A in dental epithelium at early stages of human tooth development suggesting their roles in odontogenesis . The mutations of genes exclusively expressed in embryonic dental epithelium have been shown to cause tooth agenesis 29 - 31 . The majority of our mutations observed were truncating mutations 19 - 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients consulted for diagnosis by NGS are from all specialties, including neurologists (Veeravigrom et al, ), dentists (Intarak, Theerapanon, Ittiwut, et al, ; Nowwarote et al, ; Porntaveetus, Nowwarote, et al, b; Porntaveetus, Osathanon, et al, ), orthopedists, endocrinologists (Sangsin, Srichomthong, Pongpanich, Suphapeetiporn, & Shotelersuk, , ), hematologists (Ittiwut et al, ; Ittiwut et al, ), dermatologists (Intarak, Theerapanon, Srijunbarl, et al, ; Panmontha et al, ; Panmontha et al, ), immunologists (Suratannon et al, ), syndromologists (Porntaveetus, Abid, et al, ; Porntaveetus, Srichomthong, Ohazama, Suphapeetiporn, & Shotelersuk, ; Porntaveetus, Theerapanon, Srichomthong, & Shotelersuk, ), biochemical geneticists (Chaiyasap et al, ; Phowthongkum, Ittiwut, & Shotelersuk, ; Porntaveetus, Srichomthong, Suphapeetiporn, & Shotelersuk, ), oncologists (Sahakitrungruang et al, ), and radiologists (Yeetong, Phewplung, Kamolvisit, Suphapeetiporn, & Shotelersuk, ). We have observed a wide range of yields depending on disease groups, recruitment criteria and, very importantly the cooperation of the clinicians and the bioinformaticians.…”
Section: Rare and Undiagnosed Diseasesmentioning
confidence: 99%